Cost Effectiveness Analysis Using Antibiotics of Cefixime and Cefotaxime for Diarrhea Patients at X Hospital in 2017 - Gayatri Citraningtyas; Ranny Inggrid Ruru; Amelia Nalang (Faculty of Pharmacy, Universitas Gadjah Mada)
Diarrhea is a disease characterized by a change in the shape and consistency of stools, from soft to liquid, and increased frequency of bowel movements, which happen three times or more in a day. Different use of antibiotics by patients results in patient’s medical cost increase. The use of expensive antibiotics does not guarantee the effectiveness of patient care, therefore a research needs to be done to determine which antibiotic therapy is more cost effective between cefixime and cefotaxime antibiotics in hospitalized diarrhea patients in X hospital. This research was descriptive research with retrospective data retrieval. This research was conducted at Medical Record Installation and Fund mobilization department of X hospital from November 2017 - Maret 2018. The samples in this study were 42 patients with 21 patients using Cefixime and 21 patients were using an Cefotaxime. Data was analyzed descriptively in table form. The results showed that the more cost-effective therapy between Cefixime and Cefotaxime in the treatment of diarrhea in X hospital was therapy with Cefixime antibiotic, which can be seen from ACER (Average Cost-Effectiveness Ratio) Cefixime Rp. 323.428,14/day compared with Cefotaxime ACER value of Rp. 477.180,26/day for each increase in effectiveness. The lowest ICER value on Cefixime was Rp. -50.565,8.-